The orphan nuclear receptor EAR-2 (NR2F6) inhibits hematopoietic cell differentiation and induces myeloid dysplasia in vivo - Christine V. Ichim; Dzana D. Dervovic; Lap Shu Alan Chan; Claire J. Robertson; Alden Chesney; Marciano D. Reis; Richard A. Wells (BMC, 2018)
Abstract Background In patients with myelodysplastic syndrome (MDS), bone marrow cells have an increased predisposition to apoptosis, yet MDS cells outcompete normal bone marrow (BM)-- suggesting that factors regulating growth potential may be important in MDS. We previously identified v-Erb A related-2 (EAR-2, NR2F6) as a gene involved in control of growth ability. Methods Bone marrow obtained from C57BL/6 mice was transfected with a retrovirus containing EAR-2-IRES-GFP. Ex vivo transduced cells were flow sorted. In some experiments cells were cultured in vitro, in other experiments cells were injected into lethally irradiated recipients, along with non-transduced bone marrow cells. Short-hairpin RNA silencing EAR-2 was also introduced into bone marrow cells cultured ex vivo. Results Here, we show that EAR-2 inhibits maturation of normal BM in vitro and in vivo and that EAR-2 transplant chimeras demonstrate key features of MDS. Competitive repopulation of lethally irradiated murine hosts with EAR-2-transduced BM cells resulted in increased engraftment and increased colony formation in serial replating experiments. Recipients of EAR-2-transduced grafts had hypercellular BM, erythroid dysplasia, abnormal localization of immature precursors and increased blasts; secondary transplantation resulted in acute leukemia. Animals were cytopenic, having reduced numbers of erythrocytes, monocytes and granulocytes. Suspension culture confirmed that EAR-2 inhibits granulocytic and monocytic differentiation, while knockdown induced granulocytic differentiation. We observed a reduction in the number of BFU-E and CFU-GM colonies and the size of erythroid and myeloid colonies. Serial replating of transduced hematopoietic colonies revealed extended replating potential in EAR-2-overexpressing BM, while knockdown reduced re-plating ability. EAR-2 functions by recruitment of histone deacetylases, and inhibition of differentiation in 32D cells is dependent on the DNA binding domain. Conclusions This data suggest that NR2F6 inhibits maturation of normal BM in vitro and in vivo and that the NR2F6 transplant chimera system demonstrates key features of MDS, and could provide a mouse model for MDS.